The Impact of Physical Activity on Childhood and Adolescent Cognitive Growth and its Link to Obesity - Manjiri Rhishikesh Babar; Mandar Ambike; Suresh Babu Kondaveeti (Journal of Pharmacy and Bioallied Sciences, 2025)
Background: The impact of physical activity and obesity on the human brain has long been a debatable matter. There are several studies that either accept or refute the relation. It is influenced by several factors like age, gender, and socioeconomic status. This research aims to dwell on these topics Material and Methods: An observational analytical study was conducted. A questionnaire was circulated among parents of children between 3 and 18 years of age. Incomplete forms and children suffering from previous diseases were excluded. The variables were compared, analyzed, and interpreted by using SPSS software. Results: Considering the exclusion criteria, a total of 292 responses were considered. A bivariate cross tabulation was made comparing variables such as age group, gender, and socioeconomic status with engagement in physical activity. It was found that kindergarten children (81.8% of the kindergarten children) participated more in physical activity as compared to higher age groups. More boys (79.4%) participated in physical activity as compared to girls (60.7%). A weak correlation of -0.111 was found between engagement in physical activity and time taken to complete a topic. Conclusion: The findings implied that younger children engaged more in physical activity. Males were found to be more physically active as compared to females. Children with sedentary lifestyle and a higher body mass index were found to take a longer time to understand a concept.